Language Assessment Literacy in EFL Edupreneurship Among Lecturers at Muhammadiyah University of Makassar and Samarkand Institute - Hambali, Uyunnasirah; Natsir, Ratu Yulianti; Akib, Erwin; Valeryevna, Petrosyan Nelya (Aptisi Transactions On Technopreneurship (ATT), 2024)
Language Assessment Literacy (LAL) is a crucial competency for language teachers, encompassing the knowledge and skills required to effectively conduct assessment activities. This research aims to explore the perceptions of EFL lecturers at Muhammadiyah University of Makassar and Samarkand Institute regarding different types of LAL, and how technological innovations and digital tools can enhance these skills. The study utilized a purposive sampling technique to select ten lecturers from both institutions, who participated in an online questionnaire focusing on two main categories: "knowledge and skills." Within these categories, assessments were divided into digital assessment, test efficacy and accuracy, language proficiency, instructional assessment methods, grading standards, and test outcomes. The results indicated that the majority of participants predominantly employed methods of instructional assessment (87.5%) and test efficacy and accuracy (82.5%). Other areas, such as language proficiency (72.5%) and test outcomes (75%), were also significantly applied. Digital assessment and grading standards were less utilized (70% and 67.5%, respectively). The findings suggest the need for EFL lecturers to be equipped with the necessary knowledge and skills to implement quality assessments effectively. Integrating SDGs, particularly Goal 4 (Quality Education), this study underscores the importance of enhancing teacher competencies through innovative technologies and digital tools to achieve inclusive and equitable quality education. By improving LAL, educators can better support students' learning outcomes and contribute to sustainable educational practices.